Effective Disinfectants for Coccidioides immitis and C. posadasii - Vogler, Amy J. (Appl Biosaf, 2015)
The lack of published data on effective disinfectants and contact times for use on the fungal pathogens Coccidioides immitis and C. posadasii prompted the authors to investigate the fungicidal activity of three commonly used laboratory disinfectants on arthroconidia harvested from C. immitis strain 2009. They tested the ability of 10% bleach, 70% ethanol, and Vesphene(®) IIse to inactivate 10(7) arthroconidia in an aqueous suspension within 1, 2, 5, 10, or 20 minutes of contact time. Both 10% bleach and 70% ethanol provided a 7-log(10) reduction in arthroconidia in less than 1 minute, with no growth observed at any of the tested time points. Vesphene(®) IIse was less effective, providing a 6-log(10) reduction in arthroconidia after 5 minutes, but was unable to completely inactivate all of the arthroconidia, even after 20 minutes of contact time.